Number of pregnancies and season of calving influence the production and reproduction traits in Nili-Ravi buffalo - S, Dhandapani; Vohra, Vikas; Chhotaray, Supriya; Kumar, Sanjay; Singh, K P; Kataria, R S (Indian Journal of Dairy Science, 2020)
Production and reproduction traits in Nili-Ravi buffaloes maintained at the ICAR-Central Institute for Research on Buffaloes, Sub-campus, Nabha, Punjab, were analysed to study the impact of Number of pregnancies (parity) and season of birth on performance. The least squares method was used to elucidate the effect of parity and season of calving on production and reproduction traits. The overall least squares means of production traits, 305 days or less milk yield, total lactation milk yield, and lactation length were 2603.22±47.66 kg, 2691.82±56.20 kg, and 305.72±4.95 days, respectively, and reproduction traits age at service, age at calving, service period, calving interval and dry period were 1418.76±16.60 days, 1741.30±18.52 days, 163.52±7.33 days, 466.55±6.70 days and 157.11±4.18 days, respectively. The parity had shown significant effect on all studied production and reproduction traits. However, the season of calving impacted only dry period in Nili-Ravi buffaloes.